PENGARUH KETAATAN ATURAN AKUNTANSI, ASIMETRI INFORMASI, MORALITAS INDIVIDU TERHADAP KECENDERUNGAN KECURANGAN (FRAUD) AKUNTANSI - Puspasari Ni Luh; Putra Cokorda Gde Bayu (Hita Akuntansi dan Keuangan, 2022)
The purpose of this study was to examine the effect of compliance with accounting rules, information asymmetry, individual morality on the tendency of accounting fraud at the Village Credit Institution (LPD) Payangan Regency. The participants in this study were all members of the LPD in Payangan District as many as 95 people. Purposive sampling was used to determine the sample size, which resulted in a total of 57 persons. Following the instrument test and the classical assumption test performed, multiple linear regression analysis, determination, t test, and F test were used to evaluate the data. The findings of the investigation reveal that accounting standards must be followed have a detrimental impact based on likelihood of accounting fraud in the workplace Village Credit Institution in Payangan District. Information asymmetry and individual morality have a positive and significant impact based on likelihood of accounting fraud at Village Credit Institution in Payangan Regency. It is recommended that LPDs in Payangan District are able to maintain and improve compliance with accounting rules so that LPDs run according to the expected goals.